The Use of Peer-Assessment in Enhancing ESP Students’ Speaking Ability - Hasnani Hasnani; Muh. Hosni Mubarak (Universitas Cokroaminoto Palopo, 2020)
The English for Specific Purpose students assumed that the speaking ability is the most challenging item to learn English because the English learning class and the environment are unsupportive to the students to speak in English. This research aimed to describe whether the peer assessment improves the ESP students' speaking ability or not. Thus, the researchers conducted experimental research by using a peer assessment method to check the improving speaking ability of ESP Students. This research involved 30 second-semester students of Teknik Laboratorium Medis at Universitas Megarezky. The data was analyzed from the assessment, interviews, observation, and field notes during the study. The result showed that the average of students' was 67.3 before applying peer assessment, while the percentage of students' score was 82 after using peer assessment. The speaking ability increased in the post-test after using peer assessment. The peer assessment can improve the speaking ability of ESP students' performances. This study concludes that the implementation of peer-assessment improves the speaking ability performance of ESP students. Although this research proves that peer assessment significantly increases speaking ability, but the next study is urgently needed, especially for ESP students. The researchers suggest tor further analysis to have more peer assessment techniques and apply peer assessment in different ways in ESP students.